Hannah Arendt And Amartya Sen On Freedom - Leuehaq, Timoteus Ata; Fatlolon, Costantinus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2024)
This article discusses Arendt and Sen’s concept of freedom. The two thinkers discuss this topic in the context of social and political life. The main question that this article addresses is: “What are the similarities and differences between Arend and Sen on freedom?” Using a critical analysis approach, this article argues that although these two thinkers come from different eras their thoughts on freedom have some agreements and specific differences. Their agreement here points to some similarities, supports and connections between their thoughts whereas the different positions here refer to some specific ideas which is mainly due to some specific or peculiar context of their ideas on freedom. The similarity between the two thinkers is that they indirectly agree that freedom is concerned with the capability or all the possible ways to be and to do, and the absence of repressive policies. Nonetheless, Arendt’s reflections on freedom were not in an atmosphere of socio-political emergency marked very seriously poverty, injustice, tyranny, and political pressure. Sen, on the other hand, was precisely in that atmosphere: the problem of welfare, contemporary poverty, injustices, contemporary capitalism.